Peran Bapelitbang Dalam Meningkatkan Penerimaan Pajak Daerah - Rikardus Weo; Antonius Philipus Kurniawan; Vinsensius Ama Muda (Jurnal Projemen UNIPA, 2022)
This research aims to determine the role of planning, research and development agency in increasing local tax revenues in Sikka Regency. The data collecting techniques used in this writing were observation, interviews and documentation at Bapelitbang, especially in the economy sector and natural resources (PSDA) which has an obligation to monitor and evaluate the receipt of regional original income including regional tax revenue. The results of this writing showed that Bapelitbang also plays a role in increasing local tax revenues through the preparation of local tax plans that take into account factors such as revenue potential, efficiency, and service quality. On the oher hand, the economic and natural resources sectors must perform a large number of duties, but this was still a problem due to a lack of personnel in these sectors. This condition makes it difficult for them carry out theeir role in monitoring and coordinating regional tax revenues.